An evaluation method for measuring SPL and mode shape of tire cavity resonance by using multi-microphone system. (April 2016) - Tanaka, Yohsuke; Horikawa, Shogo; Murata, Shigeru
Abstract: This paper presents an evaluation method for measuring the sound pressure level and mode shapes of tire cavity resonance by using a multi-microphone system. Two commercial tires were evaluated to compare abilities of noise suppression by means of this method in the range of the first resonance from 200 to 260 Hz. One tire was a special tire that suppresses tire cavity resonance with polyurethane foam mounted on the tire's inner liner. The other tire was a normal tire with no polyurethane foam. The mode shape change from vertical to horizontal direction in both tires. However, the sound pressure level of the special tire was lower than the normal tire at all frequencies.